Factors Affecting Learning Readiness and Academic Performance among Students of Sub-Degree and Degree Programmes in Kaduna Metropolis - SULEIMAN, Abdurrazaq (Ilorin Journal of Education, 2024)
The study examined the extent to which learning readiness affects students’ academic performance in sub-degree and degree programmes in Kaduna metropolis. Cross sectional survey research design was adopted on a four-point Likert scale. The research instrument used was a questionnaire. Fifteen items that make up the questionnaire were structured in content, construct and predictive validity of the study. The reliability of the instrument was established through test-retest method with Spearman correlation co-efficient 0.82. Sample size of the study was 153 respondents from students and lecturers in sub-degree and degree awarding institutions in Kaduna metropolis. Mean scores and standard deviation were used for descriptive statistics while t-test and percentage were used for inferential statistics. The major findings revealed that entry behaviour, class attendance and reading culture (in their inadequacies) were each contributing more than 75% to poor academic performance of students. Furthermore, the hypotheses confirmed absence of significant difference in responses between sub-degree and degree institutions, concerning negative effect of entry behaviour, class attendance and reading culture on students’ academic performance in Kaduna metropolis. The major recommendations advocate sustainability of Post-UTME tests, pre-ND programmes and pre-degree programmes in bridging quality substance deficiencies occasioned by accustomed cheating at SSCE used for entry qualification into tertiary institutions of learning.